Revisiting the Intellectual Capital–Performance Nexus: Evidence on the Moderating Influence of Competitive Advantage - Ayu Setyaningrum; Bima Cinintya Pratama; Sri Wahyuni; Dwi Winarni (E-Jurnal Akuntansi, 2025)
This study investigates the influence of intellectual capital components—namely human capital, structural capital, and physical capital—on the financial performance of banking institutions, with a specific focus on the moderating effect of competitive advantage. The research draws on a sample of banking firms listed on the Indonesia Stock Exchange and the Commercial Bank of Malaysia for the period 2020 to 2023. A total of 264 firm-year observations were obtained through purposive sampling based on established selection criteria. Panel data regression analysis, conducted using Stata software, reveals that both human capital and physical capital exert a positive and statistically significant effect on return on assets (ROA). In contrast, structural capital and competitive advantage exhibit no direct significant relationship with ROA. However, competitive advantage is found to significantly moderate the relationship between physical capital and financial performance, suggesting its role in amplifying the value derived from tangible assets.